Does an adequate use of emotions influence the development of our sons and daughters? (Journal of Parents and Teachers, 2014)
Both parents and teachers want for our children to develop in an integral way. This involves educating them not so much intellectually, but above all, emotionally. This article offers ideas for educating emotionally properly.
Keywords: emotions; integral development; emotional intelligence; emotionally intelligent education.